Resistance and genetic divergence of wild cotton genotypes under attack by sucking pests - Oliveira, Carlos Eduardo da Silva; Witt, Travis Wilson; Jalal, Arshad [UNESP]; Hoffmann, Lúcia Vieira; da Silva Leite, Gabriel [UNESP]; de Oliveira Neto, Sebastião Soares [UNESP]; Zoz, Tiago (Springer Nature, 2024)
Sucking pests in recent years have become a concern for cotton cultivation worldwide. In this sense, the study aimed to identify cotton genotypes resistant to sucking insect attacks. The experiment was conducted in Cassilândia in the 2016/2017 harvest, using thirteen cotton genotypes. During the crop season, weekly samples of cotton aphid, Silverleaf whitefly, and cotton stainer were obtained. The data obtained were subjected to the analysis of variance and the Scott-Knott clustering algorithm at the level of 5% probability. Cotton genotypes G. thuberi, Gba04, PAYM, G. trilobum, Gba01, Gba02, and Gba03 had the lowest populations of adults and nymphs of Silverleaf whitefly in the period. The genotypes PAYM, TX25, TX16, TX19, GBA03, IAC19, CO417, and EMPI were the most preferred for feeding by the cotton aphid. The cotton genotype IAC19 was the least preferred for feeding by cotton stainer; conversely, PAYM, Gba01, and TX25 were the most preferred for feeding by these insects. G. thuberi, Gba04, PAYM, G. trilobum, Gba01, and Gba02 were less harmed by the attack of Silverleaf whitefly adults and nymphs; however, Gba01, Gba02, and Gba04 were the least preferred for feeding by cotton aphids, and IAC19 was the least preferred for feeding by cotton stainer. The cotton aphids and Silverleaf whitefly adults and/or nymphs have a high negative correlation with cotton yield, making the pests more harmful to the harvest. Graphical Abstract: (Figure presented.)
Keywords: Cotton aphid; Cotton stainer; Genetic distance; Silverleaf whitefly